A survey of UK beekeeper’s Varroa treatment habits - Valentine, Alexandra; Martin, Stephen J. (PloS one, 2023)
The global spread of the parasitic mite Varroa destructor instigated a substantial decline in both managed and feral honeybee ( Apis mellifera) colonies mainly across the Northern hemisphere. In response, many beekeepers began to treat their colonies with chemical acaricides to control mite populations in managed colonies. However, some countries or beekeepers allowed their bees to develop mite-resistance by adopting a “treatment-free” approach, rather than using selective breeding programs. Yet, the distribution and proportion of beekeepers either treating or not within the United Kingdom (UK) is unknown, as it is in most Northern hemisphere countries. Therefore, the aim of this study was to conduct a beekeeper survey to determine the current treatment strategies within the UK. We gathered 2,872 beekeeper responses from an estimated 30,000 UK beekeepers belonging to 242 bee-associations in the winter of 2020/21. The survey indicated that the majority (72–79%) of UK beekeepers are still treating their bees for Varroa , typically twice-yearly using chemical-based methods. Six percent or 1,800 UK beekeepers were treatment-free for six years or more. This is reflected by our finding that 78 associations out of 242 consist of responders who entirely treated, while only four associations had more than 75% of their members that were non-treating. Overall treatment status was not affected by association currently. Using the baseline data from this survey it will be possible in the future to observer if a shift towards treatment-free beekeeping occurs or not.